Evaluation of socio-economic characteristics, preference and consumption pattern of meat among the inhabitants of Yewa in Ogun State Nigeria (2016)
This study was conducted in Yewa zone of Ogun state to investigate the socio-economic characteristics, preference and consumption pattern of meat among the inhabitants who are rural dwellers. Primary data were collected through 300 structured questionnaires covering 12 selected rural towns. The variables measured included age, sex, educational and marital status, household size, religion, occupation, income, preference for meat, factors influencing meat preference, meat consumption pattern and constraints for meat consumption in the study area. Data collected were analysed with frequency percentages and Garrett’s ranking technique and validated for reliability. The results showed that (30.01%) of household consumed meat were mostly youth who were mostly (54.0%) females that attained secondary education (32.3%) while 67.7% of them had one form of education or the other. (30.7%) were married with highest (29.3%) household size, Christians (40.7%) and traders (28.3%) and earned monthly income (29.0%) between N10, 000-N30, 000. Also majority (95.0%) preferred beef (87.5%) and chicken while (56.7%) preferred pork. Majority with 64.6 scores consumed meat perhaps for its nutritional value and taste (63.5) score without minding the price 56.8 score while tenderness was not the hindering factor (50.2) score for consuming meat in the study area. High percentage of the respondents consumed meat of any type but consume more (25.0%) of beef than pork (57.7%) as low percentage (19.3%) of the total respondents would not consume meat. Majority of them strongly disagreed that no constraint associated with meat preference and consumption would deter them from consuming meat. It was recommended therefore, that household in the study area be encouraged by government extension agents to utilize part of their income to purchase meat to be included in their diets to improve the quality. Also there is need to conduct a research to investigate low percentage consumption meat by the inhabitants of Yewa zone, the study area.